2014
DOI: 10.9790/2380-07512730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cassava Peel – Cassava Leaf Meal Based Diets for Milk Production by the West African Dwarf Goats in South Eastern Nigeria

Abstract: An experiment was conducted to determine the effects of cassava peelcassava leaf meal based diets on the milk yield and composition of WAD goats. Four lactating WAD does were housed individually in pens and were assigned to the experimental diets in a 4x4 Latin Square Design Experiment and fed for 56days. Drinking water was offered liberally. Milk yield (MY) was measured and analyzed weekly for total solids (TS), butterfat (BF), crude protein (CP), solids-not-fat (SNF), lactose, ash and milk energy. MY, BF, CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
1
4
2
Order By: Relevance
“…The crude protein of the feedstuffs in this study was higher than the crude protein reported by Babayemi et al(2010). The crude protein content of cassava leaves in this study was higher than that reported by Ukanwoko and Ibeawuchi (2014). The crude protein content reported for yam peels, cassava peels and ripe plantain peels by Kalio et al (2013) compares favourably with those reported in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…The crude protein of the feedstuffs in this study was higher than the crude protein reported by Babayemi et al(2010). The crude protein content of cassava leaves in this study was higher than that reported by Ukanwoko and Ibeawuchi (2014). The crude protein content reported for yam peels, cassava peels and ripe plantain peels by Kalio et al (2013) compares favourably with those reported in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…Dry matter content of the dietary models across the treatments ranged between 85.01% and 86.50%. This value range is comparable to 87.52% reported by Ukanwoko and Ibeawuchi [13] for cassava based diets fed to WAD goats. But lower than 90.30-91.84% reported by Guimaraes et al [14] for diets containing cassava peels fed to goats.…”
Section: Discussionsupporting
confidence: 85%
“…More so, all the diets seemed to be isoproteic due to similar values obtained. Crude fiber content obtained was higher than 16.60% reported by Ukanwoko and Ibeawuchi [13]. The values of ether extract are comparable across the dietary treatment but slightly lower than 6.04% reported by Kalio et al [16] for urea treated cassava peel fed to WAD goat.…”
Section: Discussioncontrasting
confidence: 44%
“…However, Indonesia national minimum standard for fresh milk are fat 3%, SNF 8%, protein 2.7%, and TS 11% [7]. Unchanged milk volume on the supplementation of cassava peels, cassava leaves, and cassava roots was also reported in the studies of Petlum et al [8], Lunsin et al [9], and Ukanwoko and Ibeawuchi [10]…”
Section: Resultsmentioning
confidence: 89%